Application of the Khiyar Contract in Purchasing Practices (Online) - Nuraini, Yulia; Kurniawan, Kurniawan (Zabags International Journal of Economy, 2024)
In this research, online buying and selling transactions at Purnama Muslim Store need to apply Khiyar as a form of protection for buyers and guarantee customer satisfaction, however Purnama Muslim Store has not implemented Khiyar fully and is not in accordance with Muamalah Fikih. The aim of this research is to find out how Khiyar is implemented in online buying and selling carried out by Purnama Muslim Store. The type of research used is qualitative research. From the research results, it was found that the implementation of Khiyar in online buying and selling practices carried out by Purnama Muslim Store has implemented Khiyar, but not completely. The Khiyar that is applied is Khiyar Conditions, where the buyer is allowed to require an exchange of the product purchased if something happens to the product purchased. Then Khiyar 'Aib, where buyers are allowed to exchange products if there is a defect or wrong color in the product purchased. Then Khiyar Ru'yah, where buyers who shop online and only see product photos are allowed to exchange goods if there is a discrepancy in the product.